Religiosity Memoderasi Pengaruh Machiavellianism Dan Orientasi Etika Terhadap Tax Evasion - Nadya Salsabila; Zumratul Meini (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the effect of machiavellianism, ethical orientation (idealism and relativism) on tax evasion and the moderating role of religiosity. The research method used is quantitative. The data collection technique of this research is primary data by distributing questionnaires. The population in this study were DKI Jakarta Individual Taxpayers. The sampling technique used Purposive Sampling with a total of 100 individual taxpayers. The data analysis method used in this study is Structural Equation Modeling (SEM) using the SmartPLS version 3.2.9 application. The results showed that machiavellianism has no effect on tax evasion, while idealism and relativism affect tax evasion, then religiosity does not moderate the effect of machiavellianism while religiosity moderate idealism and relativism on tax evasion. Based on these findings, it shows that machiavellianism does not always lead someone to engage in tax fraud. Furthermore, someone who has an understandin of idealism, when faced with the reality of weak laws in force will cause tax evasion. Furthermore, the attitude of relativism has a positive effect on tax evasion. This happens because someone who has a relativism attitude will tend to ignore the prevailing moral rules, thus encouraging tax evasion behavior. Furthermore, religiosity cannot moderate the influence of machiavellianism on tax evasion and religiosity can moderate the influence of idealism and relativism on tax evasion. Keywords: Machiavellianism, Ethical Orientation, Tax Evasion, and Religiosity